Peran Media Sosial dalam Membangun Kesadaran Kesehatan Mental Generasi Z - Ilmi Sila Ayu; Febi Ramadhani Rusdin; Muhammad Taslim; Felisianus Novandri Rahmat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to examine the role of social media in increasing mental health awareness among Generation Z. As a digital-native cohort, Gen Z relies heavily on platforms such as Instagram, TikTok, and X (formerly Twitter) for information, connection, and self-expression. While these platforms can serve as tools for mental health education and peer support, excessive use has also been linked to increased anxiety, depression, and poor self-image. This study seeks to explore the dual function of social media both as a supportive environment and as a risk factor for mental well-being in young people. This study employed a systematic literature review method by analyzing 20 scientific articles published between 2019 and 2025. Articles were collected from databases such as Google Scholar, Scopus, and accredited national journals (SINTA), focusing on studies that discuss mental health, social media, and Generation Z. Inclusion criteria included research articles with relevant themes, peer-reviewed status, and publications in either Indonesian or English. The findings reveal that while prolonged passive social media use contributes to increased symptoms of anxiety and depression, intentional and informed use can promote mental health awareness. Effective strategies identified in the reviewed literature include storytelling, peer support groups, the use of micro-influencers, and the delivery of accessible mental health content in visual and interactive formats. Social media plays a complex role in Gen Z’s mental health landscape. To maximize its potential for positive impact, digital literacy and empathetic communication strategies must be integrated into public health and educational initiatives. Collaborative efforts between educators, content creators, and policy makers are essential in building a supportive and safe digital environment for youth.